Maternal uniparental heterodisomy of chromosome 14: chromosomal mechanism and clinical follow up. Issue 7 (1st July 2000) - Sanlaville, D; Aubry, M C; Dumez, Y; Nolen, M C; Amiel, J; Pinson, M P; Lyonnet, S; Munnich, A; Vekemans, M; Morichon-Delvallez, N
Abstract : To our knowledge, 22 cases of chromosome 14 maternal uniparental disomy (UPD(14)mat) have been reported so far. The majority of cases were ascertained because of an abnormal phenotype associated with a Robertsonian translocation involving chromosome 14. We report here on a child with UPD(14)mat detected prenatally and resulting from trisomy rescue in a maternal meiosis I non-disjunction trisomic zygote. After four years of clinical follow up, in addition to intrauterine growth retardation (IUGR), only short stature and small hands and feet were observed. These clinical data as well as the ascertainment and mechanism of origin of UPD(14)mat were compared with those observed in previously reported cases. It appears that the clinical spectrum of UPD(14)mat is milder in our patient than in patients with UPD(14)mat resulting from other chromosomal mechanisms. In addition, a hypothesis based on abnormal imprinting is proposed to explain the variability of the UPD(14)mat.